Membrane‐Supported Multichannel Microfluidic Solvent Extraction System. Issue 4 (15th March 2017) - Prechtl, Carolin; Kraut, Manfred; Franzreb, Matthias; Brenner-Weiß, Gerald; Dittmeyer, Roland
Abstract: Although microfluidic solvent extraction (µSX) is a recent field in separation, its application is still limited to single‐channel microfluidic devices. However, the industrial application of microheat exchangers has already proven that parallelization of microchannels is an important tool to increase the specific device efficiency. Hence, in this study, a multichannel system for µSX is introduced. As a model process, D, L ‐5‐phenylhydantoin was extracted from ethyl acetate into aqueous buffer. By means of different experimental setups, the potential and limitations of membrane‐supported multichannel µSX were investigated. The reactor dimensions perpendicular to flow and transmembrane mass transport are the most challenging factors for the introduced device. Abstract : Membrane‐supported multichannel microfluidic solvent extraction allows popular batch catalysis to be switched to continuous‐flow processing. The polymeric membranes stabilize the scaled‐up liquid‐liquid interface. Different experimental setups are used to analyze resulting mass transport and determine the main limitations and advantages of each setup.